Results of Femtosecond Laser-Assisted Descemet Stripping Automated Endothelial Keratoplasty - Mohamed H. Hosny; Ayah Marrie; M. Karim Sidky; Sherif GamalEldin; Mohsen Salem (Journal of Ophthalmology)
Purpose. To evaluate femtosecond laser in DSAEK surgery as an improvement to manual DSAEK. Settings. Department of Ophthalmology, Cairo University. Design. A retrospective observational clinical study. Methods. 20 eyes with SBK and Fuchs’ dystrophy underwent a Femto-assisted DSAEK by laser cutting of two matching posterior stromal discs in the recipient and donor corneas and then fitting the donor disc in the posterior corneal defect of the recipient using Busin’s glide or Terry forceps. Results. Corneal thickness decreased significantly from a mean of 900-micron preoperative values (900.7 m) to 562 m postoperatively. Evidence of side healing was documented by OCT. One patient had a double AC, one patient had an air interface entrapment “Double Bubble,” one patient had a fungal infection and was treated by a therapeutic penetrating keratoplasty, and one patient had a CMO. Conclusion. Femtolaser-assisted DSAEK may be superior to manual techniques as it offers better centration, thinner graft/host complex, earlier corneal detergecense, and stronger healing. This study was registered at Researchregistry.com with a UID: researchregistry2274.